Ginger and Petunia - Polacco, Patricia (Philomel Books, 2007)
When her beloved Ginger, a piano-playing socialite and very snappy dresser, makes a last-minute trip to London not knowing her housesitter has cancelled, Petunia the pig does more than fend for herself, she becomes Ginger.